HARZBURGITE-DUNITE-ORTHOPYROXENITE SUITE AS A RECORD OF SUPRA-SUBDUCTION ZONE SETTING FOR THE OMAN OPHIOLITE MANTLE - Tamura A.; Arai S. (My University, 2006)
We found a harzburgite-dunite-orthopyroxenite suite from the West Jizi block in the northern Oman ophiolite as a record of supra-subduction zone magmatism in the mantle. The orthopyroxenite has features of parallel dikes, each dike being 10-30 cm thick and in direct contact with the host harzburgite. The orthopyroxenite is composed of orthopyroxene (> 95 vol.%), clinopyroxene (< 5 vol.%) and trace spinel (< 1 vol.%), and is free from olivine. All rocks from the suite are characterized by high Cr# [= Cr / (Cr + Al) atomic ratio] of spinel (Cr# ≥ 0.65). The Fo content of olivine is relatively low, 89.9 to 91.1, in harzburgite and dunite. Clinopyroxenes are very low in incompatible elements and show LREE enrichment in orthopyroxenite and host harzburgite. Similar trace element concentrations of clinopyroxenes in the harzburgite and orthopyroxenite suggest their genetic linkage: the harzburgite is a residue of a partial melting, and its extracted melt formed orthopyroxenite dike. The melt in equilibrium with clinopyroxene is similar in trace-element characteristics to boninite. The mineral chemistries indicate that the harzburgite experienced higher degree of partial melting than abyssal peridotite. LREE-enriched melt and/or fluid assisted the high-degree melting. These lines of evidence indicate an involvement of arc magma in the rock suite genesis, i.e. a supra-subduction zone setting experienced by the Oman ophiolite mantle. © 2006 Elsevier B.V. All rights reserved.
Keywords: ARC-RELATED MANTLE; BONINITE MAGMA; DEPLETED HARZBURGITE; HIGH-CR# SPINEL; OMAN OPHIOLITE; ORTHOPYROXENITE